Menakar Ukuran Ideal Pembatasan Hak Guna Usaha (HGU) untuk Badan Hukum sebagai Upaya Mengatasi Ketimpangan Penguasaan Lahan Perkebunan Kelapa Sawit di Indonesia - Aisyah Syafa Carolina; Teza Salih Mauludin; Meiza Hafilda (CV Rewang Rencang, 2022)
Land rights basically need to be limited. Article 17 paragraph (1) of the Agrarian Law mandates restrictions on ownership and control of land rights by one family or legal entity. This study aims to analyze the regulation of HGU restrictions for legal entities. This normative juridical research uses a descriptive-analytical approach. The study results show that the status quo of the regulation of HGU restrictions for legal entities is only related to licensing. Still, the HGU restrictions for legal entities do not yet exist. This legal vacuum has resulted in unequal land tenure for oil palm plantations in Indonesia.